THE bei CONSTRUCTIONS IN CANTONESE: A CORPUS-DRIVEN STUDY (Proceeding of the International Conference on Arts and Humanities, 2024)
This paper aims to analyze the Cantonese bei constructions with a ‘corpus-driven’ approach. Bei is a polysemous word with the following meanings: (a) Bei means ‘give’, which can take two nominal objects. (b) Bei is an indirect object marker. (c) Bei is a beneficiary marker. (d) Bei is a causative verb that means ‘allow’, forming a serial verb construction with another verb. (e) Bei is a passive marker in a passive construction. In this paper, around 800 examples of Cantonese bei constructions have been extracted from two corpora: Hong Kong Cantonese Corpus and Hong Kong Cantonese Adult Language Corpus. They are the Cantonese corpora freely available on the internet and reflect the usage of Hong Kong Cantonese in the 1990s. It is found that bei is always followed by one noun phrase, sometimes by two noun phrases, but there are a few patterns involving an ellipsis of the direct object or/and the indirect object, which were seldom addressed in previous studies of double object constructions involving bei. Cantonese bei constructions may result in an ambiguity of causative and passive constructions, of which the syntactic subject can be interpreted as semantic roles as “causer” or “affectee”. The interpretation often depends on pragmatic and contextual factors, which can be examined by the attested language data of the corpora.
Keywords: linguistics; Cantonese; bei constructions; corpus-driven